Infertility and marital well-being among infertile, Chinese couples from Hei Longjiang Province in China - Peng, Tao (Curtin University, 2012)
This study with the mixed method indicated infertility diagnosis, infertility stress and sexuality can be as predicators of infertile Chinese couples’ marital well-being. Additionally, social culture, traditional value of childbearing, stereotypical gender roles, stress adjustment, sexual communication, sexual satisfaction and commitment to marriage were found to have effect on infertile couples’ perceived infertility stress, understating of sexuality and their marital relationship. All of these results provided evidence for holistic intervention in infertile couple’s well-being.